2017
DOI: 10.1016/j.resuscitation.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Regular in-situ simulation training of paediatric Medical Emergency Team leads to sustained improvements in hospital response to deteriorating patients, improved outcomes in intensive care and financial savings

Abstract: These results indicate that lessons learnt by ward staff during team training led to sustained improvements in the hospital response to critically deteriorating in-patients, significantly improved patient outcomes and substantial savings. Integration of regular in-situ simulation training of medical emergency teams, including key ward staff, in routine clinical care has potential application in all acute specialties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 28 publications
0
63
0
5
Order By: Relevance
“…53 Wehbe-Janek et al 54 suggested that a simulation-based training program could overcome system barriers and augment the use of RRT. Theilen et al 55 demonstrated that regular in-situ simulation training of a paediatric RRT led to sustained improvement.…”
Section: Major Findingsmentioning
confidence: 99%
“…53 Wehbe-Janek et al 54 suggested that a simulation-based training program could overcome system barriers and augment the use of RRT. Theilen et al 55 demonstrated that regular in-situ simulation training of a paediatric RRT led to sustained improvement.…”
Section: Major Findingsmentioning
confidence: 99%
“…The first wave of expensive, high tech, highly realis c manikins now coexists with low tech, low cost and in-situ simula on regardless of a country's GDP. Concentra on on communica on skills, team dynamics and processes can result in significant skill acquisi on and improved quality of care and both outcomes are difficult to achieve or demonstrate in tradi onal educa on 7,8 modali es. The keys to the use of simula on for educa on are appropriately trained and experienced facilitators and clarity of learning objec ves and group outcomes, and measuring whether or not these are achieved.…”
Section: Roseby Rmentioning
confidence: 99%
“…13 Improvement in simulated performance, and to some extent in clinical behaviour and patient outcomes, has been Quality improvement report shown for several medical emergencies including acute ischaemic stroke. [14][15][16] In a recent article regarding simulation training in acute stroke, human factors in the stroke team is suggested as the most important rate-limiting factor in acute stroke care. 17 Simulation training directed at improving healthcare systems and patient care, so-called translational simulation, is particularly useful as part of quality improvement (QI) projects because of its potential both for diagnosing system performance and delivering simulation-based interventions.…”
Section: Introductionmentioning
confidence: 99%